Team dynamics and clinician’s experience influence decision-making during Upper-GI multidisciplinary team meetings: A multiple case study - Luijten, J.C.H.B.M.; Westerman, M.J.; Nieuwenhuijzen, G.A.P.; Walraven, J.E.W.; Sosef, M.N.; Beerepoot, L.V.; van Hillegersberg, R.; Muller, K.; Hoekstra, R.; Bergman, J.J.G.H.M.; Siersema, P.D.; van Laarhoven, H.W.M.; et al. (Frontiers in Oncology, 2022)
Background The probability of undergoing treatment with curative intent for esophagogastric cancer has been shown to vary considerately between hospitals of diagnosis. Little is known about the factors that attribute to this variation. Since clinical decision making (CDM) partially takes place during an MDTM, the aim of this qualitative study was to assess clinician’s perspectives regarding facilitators and barriers associated with CDM during MDTM, and second, to identify factors associated with CDM during an MDTM that may potentially explain differences in hospital practice. Methods A multiple case study design was conducted. The thematic content analysis of this qualitative study, focused on 16 MDTM observations, 30 semi-structured interviews with clinicians and seven focus groups with clinicians to complement the collected data. Interviews were transcribed ad verbatim and coded. Results Factors regarding team dynamics that were raised as aspects attributing to CDM were clinician’s personal characteristics such as ambition and the intention to be innovative. Clinician’s convictions regarding a certain treatment and its outcomes and previous experiences with treatment outcomes, and team dynamics within the MDTM influenced CDM. In addition, a continuum was illustrated. At one end of the continuum, teams tended to be more conservative, following the guidelines more strictly, versus the opposite in which hospitals tended towards a more invasive approach maximizing the probability of curation. Conclusion This study contributes to the awareness that variation in team dynamics influences CDM during an MDTM.